Multiple-stressor effects of warming and acidification on the embryonic development of an estuarine fiddler crab - Pardo, Juan C.F. [UNESP]; Costa, Tânia M. [UNESP] (Elsevier, 2021)
Predicted effects of anthropogenic climate change on estuarine and coastal organisms are complex, and early life history stages of calcified ectotherms are amongst the most sensitive groups. Despite the importance of understanding their vulnerability, we lack information on the effects of multiple stressors on the embryonic development of estuarine and burrowing organisms, mainly mangrove-associated species. Here, we determined the combined effects of elevated temperature and decreased pH on the embryonic development of the estuarine fiddler crab Leptuca thayeri. Initially, the microhabitat (burrow) of ovigerous (egg-bearing) females was measured for temperature, pH, and salinity, which provided control values in our laboratory experiment. Embryos at the early stage of development were subjected to cross-factored treatments of predicted temperature and pH and evaluated for development rate, survivorship, and volume until their later embryonic stage. Embryo development was faster at early and later stages of development, and survivorship was lower under elevated temperature. Embryos under reduced pH showed advanced embryonic stages at their late development stage. Higher egg volume was observed in a warmer and acidified environment, and lower volume in warmer and non-acidified conditions, indicating that embryo development is synergistically affected by warming and acidification. More than 70% of embryos developed until late stages under the multiple-stressors treatment, giving insights on the effects of a warm and acidified environment on burrowing estuarine organisms and their early stages of development.
Keywords: Abiotic factors; Climate change; Crustaceans; Embryos; pH; Temperature